The role of the transient receptor potential melastatin5 (TRPM5) channels in the pancreatic β-cell electrical activity: A computational modeling study. (October 2018) - Farashi, Sajjad; Sasanpour, Pezhman; Rafii-Tabar, Hashem
Graphical abstract: Highlights: A mathematical model of TRPM5 channel activity is proposed for the pancreatic β cell. TRPM5 reduces inter-burst interval of membrane voltage by increasing Ca 2+ influx. TRPM5 increases spike amplitude by increasing Na + current. TRPM5 increases firing frequency of membrane by affecting GABA related current. Abstract: The TRPM5 channels are transient receptor potential channels whose presence in the human pancreatic β-cell has been confirmed. The sensitivity of these channels to membrane voltage, temperature and intracellular calcium concentration and their possible role in insulin secretion has made them a focal point in research in the past decade. While experimental researches have confirmed the role of the TRPM5 channels in insulin secretion, but the underlying mechanism is still unclear. In this study, based on the experimental results of other studies, a mathematical description of the TRPM5 channel activity has been proposed which correlates the TRPM5 electrical activity to the voltage and intracellular calcium concentration. The resulting expression has been added to the existing mathematical model of the human β-cell and the enhanced model has been used for investigating the effect of the TRPM5 channel on the β-cell electrical activity. The results of our study show that the TRPM5 influences other ion channel activities through speeding up membrane depolarization. In addition, we have shown that the TRPM5 increases the amplitude and firing rate of action potentials by possibly affecting the Na + and gamma-Aminobutyric acid related currents. The results also confirm the prominent effect of the TRPM5 channels in glucose-stimulated condition.